Estudo da composição química e ecotoxicidade de óleos essenciais de interesse na aquicultura - Miura, Patrícia Tidori, 1990- (2018)
Orientadores: Felix Guillermo Reyes Reyes, Sonia Claudia do Nascimento de Queiroz